Pedagogical Creativity of a Teacher as a Basis of Formation of Creative Personality of a Pupil under the Profile School Conditions - Hanna Isayeva (Pedagogical Discourse, 2011)
The article deals with the formation of creative teacher. The attention is paid to the development of initiative and creativity of a teacher, which helps to the formation of creative personality of a pupil. The contribution of V.O.Sukhomlyns’kyi into the development of study of the theory and practice of creative teacher formation is shown.